A new species of Typhlodromus (Anthoseius) De Leon and redescription of T. (A.) montanus Chant & Yoshida-Shaul from Russia - Döker, Ismail; Khaustov, Vladimir A.; Joharchi, Omid (Zootaxa, 2021)
Typhlodromus (Anthoseius) tetraporus sp. nov., collected on grasses in Crimea, is proposed as a new species for science. The new species can be separated from all known species of Typhlodromus (Anthoseius) by the combination of following characters; peritreme extending almost to level of setae j1, four pairs of solenostomes on dorsal shield, two pairs of setae on sternal shield, a sclerotised v-shaped plate posterior to sternal shield, four pairs of pre-anal setae, a pair of small rounded pre-anal solenostomes, differentiated and larger atrium of spermatheca and eight setae on genu II. In addition, T. (A.) montanus Chant & Yoshida-Shaul (Acari: Phytoseiidae), a species only known based on its original description from Canada is reported for the first time in Russia. The new record is redescribed and illustrated based on female specimens collected from Prunus padus L. (Rosaceae) where it was associated with eriophyid mites in Pereval Seminskiy, Altai Republic. This species may be an important predator as a potential biological control agent of eriophyid mites.